Socioeconomic, intrapersonal and food environmental correlates of unhealthy snack consumption in school-going adolescents in Mumbai - Panchali Moitra; Jagmeet Madan (BMC, 2022)
Abstract Background Unhealthy snacking habits in adolescents are typically triggered by obesogenic food environments and possibly perpetuated through interactions between socio-environmental factors and personal perceptions, attitudes, and motivations to change eating behaviors. This study attempted to address the knowledge gap regarding the association of intrapersonal, socioeconomic, and food environmental characteristics with unhealthy snack consumption in Indian adolescents, presenting several targets for effective interventions. Methods A representative sample of 10-12 years old adolescents (n 712) completed a cross-sectional survey including eating habits, characteristics of school and home food environments, and perceptions related to affordability, convenience, and barriers within the food environments. The frequency of unhealthy snack consumption was assessed using a validated qualitative food frequency questionnaire. Multivariate regression analyses determined the associated factors of unhealthy snack consumption in adolescents attending private and public schools. Results The mean age of adolescents was 10.9 (1.1) years, 48.2% were girls and 53.9% attended private schools. The most frequently consumed unhealthy snacks were biscuits/ cookies (5.2d/wk) followed by wafers (3.4d/wk) and Indian fried snacks- samosa/ vada pav (2.8 d/wk). Among the public-school adolescents, the odds of unhealthy snack consumption were 0.89 times lower when meals were had frequently at the dinner table and 4.97 times higher when the perceived barriers related to the affordability of healthy snacks were greater. Maternal education (OR 0.78, 95% CI 0.66-0.82, p < 0.001), family income (OR 2.15, 95% CI 1.98-2.32, p < 0.001), availability of unhealthy snacks (OR 2.98, 95% CI 1.36-3.46, p < 0.001) and fruits (OR 0.57, 95% CI 0.49-0.69, p < 0.001) at home, having evening meals together (OR 0.71, 95% CI 0.63-0.81, p 0.031), and perceived parental control during mealtimes (OR 0.67, 95% CI 0.62-0.72, p < 0.001) were associated with unhealthy snack consumption in adolescents attending private schools. Conclusions The results highlighted a pervasiveness of unhealthy snacks in adolescents' food environments. Improving provisions and affordability of fruits and healthy snacks at schools, encouraging family mealtimes, and limiting the availability of unhealthy snacks at home whilst addressing the perceived barriers within food environments, and inculcating self-efficacy skills can improve snacking habits in Indian adolescents, irrespective of socioeconomic backgrounds.